1974
DOI: 10.1126/science.184.4144.1379
|View full text |Cite
|
Sign up to set email alerts
|

Geckos: Adaptive Significance and Energetics of Tail Autotomy

Abstract: Coleonyx variegatus is adapted to readily sacrifice its tail to predators. This adaptation is associated with characteristic tail behavior and rapid tail regeneration. There is no facultative metabolic increase associated with tail regeneration, and energy normally allocated to body growth and maintenance is diverted to tail regeneration. This supports the contention that tail behavior, autotomy, and rapid regeneration evolved as mechanisms promoting survival in terms of predator escape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1
5

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(134 citation statements)
references
References 5 publications
4
124
1
5
Order By: Relevance
“…Experimental work o n lizards and salamanders has shown that tail autotomy effectively distracts predators and prevents subjugation o f prey (Congdon et al 1974, Ducey & Brodie 1983, Dial & Fitzpatrick 1983. Nevertheless, for t h e individual, loss o f a n appendage can slow growth rate (Kuris & Mager 1975, Vitt & Cooper 1986, Smith 1990a, hinder foraging ability (Smith & Hines 1991a), decrease reproductive output ( S m y t h 1974, Maiorana 1977, Dial & Fitzpatrick 1981, Smith 1992, and lower social status (Fox & Rotsker 1982).…”
Section: Autotomy T H E Self-amputation O F a Body Part At A Breakagmentioning
confidence: 99%
“…Experimental work o n lizards and salamanders has shown that tail autotomy effectively distracts predators and prevents subjugation o f prey (Congdon et al 1974, Ducey & Brodie 1983, Dial & Fitzpatrick 1983. Nevertheless, for t h e individual, loss o f a n appendage can slow growth rate (Kuris & Mager 1975, Vitt & Cooper 1986, Smith 1990a, hinder foraging ability (Smith & Hines 1991a), decrease reproductive output ( S m y t h 1974, Maiorana 1977, Dial & Fitzpatrick 1981, Smith 1992, and lower social status (Fox & Rotsker 1982).…”
Section: Autotomy T H E Self-amputation O F a Body Part At A Breakagmentioning
confidence: 99%
“…Eighteen to 25% of blue crabs surveyed over a four year period in the Rhode River, Maryland, and 19-390/0 of blue crabs at six other sites along the eastern coast of the United States in 1989 were missing or regenerating one or more limbs. Autotomy is an effective escape response to predators (Robinson et al, 1970;Congdon et al, 1974;Medel et al, 1988;Smith, 1990a). Variation in injury levels in populations may indicate differential predation pressure (e.g., Shaffer, 1978;Ballinger, 1979;Schall and Pianka, 1980;McCallum et al, 1989) or predator efficiency (Schoener, 1979;Schoener and Schoener, 1980;Jaksic and Fuentes, 1980).…”
Section: Causal Agentsmentioning
confidence: 99%
“…Autotomy is a predator-escape strategy documented for a broad range of taxa (Fleming et al, 2007), including crabs (Bennett, 1973), spiders (Parry, 1957;Amaya et al, 2001), echinoderms (Emson and Wilkie, 1980), salamanders (Wake and Dresner, 1967), lizards (Congdon et al, 1974;Daniels, 1983;Arnold, 1984;Cooper and Vitt, 1985;Bateman and Fleming, 2009) and even some rodents (Sumner and Collins, 1918;Layne, 1972). Most commonly examined in lizards, this voluntary shedding of an appendage generally occurs in response to a predatory stimulus.…”
Section: Introductionmentioning
confidence: 99%